Dietary Concentrate-to-Forage Ratio Affects Rumen Bacterial Community Composition and Metabolome of Yaks - Yi, Simeng; Dai, Dongwen; Wu, Hao; Chai, Shatuo; Liu, Shujie; Meng, Qingxiang; Zhou, Zhenming (Frontiers in Nutrition, 2022)
This study characterized the effect of three different dietary concentrate-to-forage ratios (C:F, 50:50, 65:35, 80:20) on yak rumen fluid microbiota and metabolites using 16S rRNA gene sequencing and liquid chromatography-mass spectrometry (LC-MS). The diversity of rumen bacteria was not affected by dietary concentrate-to-forage ratio. However, the relative abundance of specific bacterial genus changed. At the genus level, higher relative abundance of norank_f__F082, NK4A214_group, Lachnospiraceae_NK3A20_group, Acetitomaculum and norank_f__norank_o__Clostridia_UCG-014 were observed in high dietary concentrate ratio (P<0.05). The relative abundances of Quinella and Ruminococcus showed opposite changes. Combined metabolomic and enrichment analyses showed that changes in dietary concentrate ratio significantly affected rumen metabolites related to amino acid metabolism (e.g., 3-methylindole, spermine, and xanthurenic acid), protein digestion and absorption (e.g., L-valine and tyramine), carbohydrate metabolism (e.g., ascorbic acid and D-glucuronic acid), lipid metabolism (e.g., 20-hydroxy-leukotriene E4, 6-keto-prostaglandin F1a, and Lipoxin B4), and purine metabolism (e.g., xanthosine, thymine, deoxyinosine, deoxyadenosine monophosphate, and ribose 1-phosphate). Correlation analysis of microorganisms and metabolites provided new insights into the function of rumen bacteria, as well as a theoretical basis for formulating more scientifically appropriate yak feeding strategies.